394 R2* and QSM Reliability for Measuring Brain Tissue Iron Concentrations. (April 2023) - Fliegner, Max; Lin, Leanne; Chaudhary, Neeraj; Pandey, Aditya S.; Keep, Richard; Xi, Guohua; Troost, Jonathan; Chenevert, Tom
Abstract : INTRODUCTION: Pathologic levels of iron have been implicated in various neurological disease states, such as Parkinson's, Multiple Sclerosis, Amyotrophic Lateral Sclerosis, and Stroke (hemorrhagic & ischemic). Using brain tissue iron concentration as a biomarker for disease progression has great potential for clinical translation; however, measuring iron concentrations non-invasively remains challenging. MRI based R2* and quantitative susceptibility mapping (QSM) values have been shown to correlate with iron levels in previous cadaveric studies. METHODS: Ten normal human subjects (ages 35-73) underwent test and retest MRI scans approximately 10 minutes apart. T1 and gradient-echo images were used to segment 7 regions of the brain bilaterally. The gradient-echo sequences were used to calculate the R2* and QSM for each region of interest. Iron concentrations were calculated from the R2* values based on R2* calibrated with a phantom. RESULTS: R2* values ranged from 19.45 Hz in the hand homunculus to 38.81 Hz in the substantia nigra and were consistent across 8-echo and 6-echo sequences. Mean QSM values ranged from -0.041 in the internal capsule to 0.046 in the globus pallidus. Calculated iron concentrations ranged from 52.1 mg/kg in the centrum semiovale to 104.6 mg/kg in the substantia nigra. Test and retest values showed consistency across brain regions for R2* with weighted coefficient variation percent of 3.9-9.6%. White matter iron concentrations ranged from 52.1-59.5 mg/kg, while deep grey nuclei iron concentrations ranged from 72.5-104.6 mg/kg. CONCLUSIONS: Our study demonstrates the ability of gradient-echo MRI to reliably measure tissue iron levels in non-disease states in healthy human subjects. Further research is needed to validate the ability of specific MRI sequences to be a surrogate biomarker in disease states.